«Jede unserer Seelen lebt nur einen Augenblick». Erzählperspektive, Wahrnehmung und Animalität in Hofmannsthals «Reitergeschichte» (Studia austriaca, 2015)
This article argues for a new understanding of Hugo von Hofmannsthal’s Reitergeschichte from 1899 through integrating the story’s animals as the perceiving pre-consciousness into its narrative voice. Through Maurice Merleau-Ponty’s pre-reflective apparatus of perception that intimately links animals and humans through their shared «past that has never been present», this article offers a phenomenological reading of animality in the narrative. Within the context of Jacques Derrida’s The Animal That Therefore I Am, this article examines the attribution of logos beyond the traditional human-animal dichotomy.